2022
DOI: 10.7759/cureus.23986
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Global Longitudinal Strain in Patients With COVID-19 Infection

Abstract: Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2, is an ongoing pandemic that has affected millions globally. Many infected patients have been noted to have cardiovascular damage. Prior to the development of clinical symptoms, the use of transthoracic echocardiography, specifically with measurements of left ventricular global longitudinal strain (LVGLS), may provide an additional prognostic marker for patients infected with COVID-19. We sought to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
2
0
3
Order By: Relevance
“…3 Few studies have investigated the prevalence of abnormal LV-GLS and its prognostic value in COVID-19 infection. [7][8][9][10] Janus et al showed similar results to our study with increased mortality observed with reduction in LV-GLS. 10 The study conducted by Baycan et al demonstrated similar results to ours with significant association between abnormal LV-GLS and in-hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
“…3 Few studies have investigated the prevalence of abnormal LV-GLS and its prognostic value in COVID-19 infection. [7][8][9][10] Janus et al showed similar results to our study with increased mortality observed with reduction in LV-GLS. 10 The study conducted by Baycan et al demonstrated similar results to ours with significant association between abnormal LV-GLS and in-hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
“…on 90 COVID-19 hospitalized patients showed a significant decline in LV GLS in nonsurvivors as compared with survivors, whereas no significant alteration in LVEF was found, indicating that COVID-19 patients might have subclinical LV dysfunction, especially in those who were exposed to a more powerful cytokine storm and hence myocardial injury, which could result in more decline in cardiac function. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal and circumferential changes diverge as myocardial disease progresses, which may contribute to the ability of strain to predict outcomes. Two-dimensional speckle tracking technology can identify myocardial dysfunction and subclinical myocardial injury ( 28 ), and studies have shown the potential value of ventricular strain assessment in COVID-19 patients ( 29 31 ). Our study found that SpO 2 , E/e' and LVGLS were the independent risk factors for mild patients progressing to moderate/severe group, and LVGLS played the most important part.…”
Section: Discussionmentioning
confidence: 99%